Noise reduction mechanisms of active noise barriers - Chen, Weisong (2013)
The sound field and acoustic power flow from different regions around an active noise barrier are analyzed using a two-dimensional numerical model. Results show that the noise reduction of the active noise barrier can be described as a combination of three mechanisms. They are acoustic energy transfer in space, acoustic energy absorption and radiated energy suppression by the secondary sources.At low frequencies, when the distance between the primary and secondary sources is well separated compared to the wavelength, the coupling is weak and the energy reflected from the shadow zone to adjacent regions by the secondary source. Acoustic energy transfer in space is the dominant mechanism. When the primary source and the secondary source are close compared to a wavelength, the mechanisms for noise reduction can be sound absorption by the secondary source and/or the radiated power of primary source is suppressed by the secondary source. The radiated power of secondary source is negative. Furthermore, both the radiated power of primary and secondary sources fluctuates acutely with the variation of distance between them. At high frequencies, the mechanism for noise reduction can be sound absorption by the secondary source. The radiated power of secondary source is negative.